Prioritas Peningkatan Kinerja Bus Listrik Metrotrans Rute 7A Kampung Rambutan – Lebak Bulus Jakarta - Agustin, Imma Widyawati Agustin; Gloria, Vanda; Ari, Ismu Rini Dwi (Indonesian Journal Publisher, 2024)
In DKI Jakarta, heavy traffic and oil-fueled car emissions are to blame for between 32% and 57% of the province's overall air pollution. The DKI Jakarta Provincial government started implementing electric buses as a proactive reaction to the carbon emission issue. One of these buses is located on Transjakarta feeder routes (non-BRT), namely Metrotrans electric bus Route 7A Kampung Rambutan - Lebak Bulus. Congestion and air pollution are the two main issues facing the transportation sector in DKI Jakarta. One mass transit option that addresses these issues is the battery-powered Metrotrans electric bus. This study's objectives are to assess the operational and service performance of Metrotrans electric buses Route 7A Kampung Rambutan - Lebak Bulus and to establish the order of importance for performance improvement. Operational performance study, which includes headway, journey time, waiting time, load factor analysis, Importance-Performance study (IPA), and Potential Gain Customer Value (PGCV) analysis, was the analysis approach employed. According to the findings, waiting times, headways, load factors, journey times, GPS, SOPs for handling crises, bus stop availability, and information about routes and routes to be served were the top priorities for performance improvement.